Expiration and Revocation of Keys for Attribute-Based Signatures - Tate, Stephen R.; Vishwanathan, Roopa (Data and Applications Security and Privacy XXIX, 2015)
Attribute-based signatures, introduced by Maji et al., are signatures that prove that an authority has issued the signer “attributes” that satisfy some specified predicate. In existing attribute-based signature schemes, keys are valid indefinitely once issued. In this paper, we initiate the study of incorporating time into attribute-based signatures, where a time instance is embedded in every signature, and attributes are restricted to producing signatures with times that fall in designated validity intervals. We provide three implementations that vary in granularity of assigning validity intervals to attributes, including a scheme in which each attribute has its own independent validity interval, a scheme in which all attributes share a common validity interval, and a scheme in which sets of attributes share validity intervals. All of our schemes provide anonymity to a signer, hide the attributes used to create the signature, and provide collusion-resistance between users.